Pengaruh Ekstrak Daun Mangrove (Bruguiera gymnorrhiza) terhadap Kadar Kolesterol Mencit (Mus musculus) Jantan Hiperkolesterolemia - Meilin Moha; Djuna Lamondo; Mustamin Ibrahim (Transbahasa, 2025)
As time progresses, advancements in technology, information, and the economy have influenced lifestyle choices, one of which is the increasing preference for consuming junk food over home-cooked meals. Junk food is typically high in fat, and excessive fat intake can lead to hypercholesterolemia, which is a significant risk factor for cardiovascular diseases. Mangrove (Bruguiera gymnorrhiza) contains bioactive compounds with antioxidant properties that have been reported to reduce total cholesterol levels. This study aims to investigate the effect of Bruguiera gymnorrhiza leaf extract as an anti-cholesterol agent in hypercholesterolemic male mice (Mus musculus). The research employed a true experimental method with a completely randomized design (CRD). Male mice were induced with a high-fat diet to develop hypercholesterolemia and were subsequently treated with different doses of Bruguiera gymnorrhiza leaf extract. Total cholesterol levels were measured before and after treatment. Data were analyzed using ANOVA followed by Duncan’s multiple range test. The results showed that the administration of Bruguiera gymnorrhiza leaf extract significantly reduced cholesterol levels, with the most effective dose being 500 mg/kg body weight, leading to a decrease of 91.4 mg/dL or 16.45%. These findings suggest that Bruguiera gymnorrhiza leaf extract has the potential to be developed as a natural anti-cholesterol agent. Further studies are recommended to explore its mechanism of action and its potential application in human health.